Altered T cell subpopulations and serum anti-TYRP2 and tyrosinase antibodies in the acute and chronic phase of alopecia areata in the C3H/HeJ mouse model. Issue 1 (October 2021) - Hashimoto, Kei; Yamada, Yoshihito; Fujikawa, Mika; Sekiguchi, Kota; Uratsuji, Hideya; Mori, Sachi; Watanabe, Hideki; Matsumoto, Tatsumi
Highlights: T cell populations and cytokine expressions differ between disease phases of AA mice. The change of T cell populations in AA mice is similar to the clinical observation. Tyrosinase-related protein 2 and tyrosinase are autoreactive targets in AA mice. Abstract: Background: C3H/HeJ mouse models progress gradually in hair loss from acute to chronic phase and reflect the symptoms of patients with alopecia areata (AA). However, the underlying pathological characteristics alteration associated with disease progression and autoantigens remain unclear. Objective: We aimed at elucidating the pathological differences between acute and chronic-AA in the C3H/HeJ mouse model. Methods: We analyzed populations of PBMCs, skin-draining lymph node (SDLN) cells, and cutaneous cells of AA mice using flow cytometry. The cytokine and chemokine expressions in the serum and skin were determined using multiplex assay and qPCR. The antibody serum levels were determined using ELISA and the antigen-specific T cells were detected using the MHC class I tetramer. Results: The CD8 + NKG2D + T and CD8 + TEM cell percentage in the chronic-AA SDLNs or among the unaffected and acute-AA mice PBMCs increased. The Th1 and CD4 + TEM cell percentage in the SDLNs and among PBMCs increased in the unaffected and AA mice. The percentage of CD8 + TEM /TRM cells and MHC class I expression increased in the lesions of acute-AA or the non-lesions and lesions of chronic-AA. The Th1 cells, dendritic cell-related cytokines, CD11c + cells and MHC class II expression increased in the skin of AA mice. The antibody levels and TYRP2 and tyrosinase-specific CD8 + T cell percentages were upregulated in AA mice. Conclusion: These results suggest that the CD8 + and CD4 + T cell subpopulations, cytokine and chemokine expressions differ between the disease phases. Moreover, TYRP2 and tyrosinase are potential autoreactive targets in the AA mouse model.